Religion and the Development of Canadian Society: An Historiographical Analysis - Clifford, N. Keith (Church history, 1969)
During the past forty years Canadian historians have viewed the relationship between religion and the development of Canadian society from three perspectives. None of these perspectives have risen out of the Canadian context; they have been imported and adapted with various degrees of success to the Canadian scene. The assistance they have given Canadian historians in perceiving and highlighting various aspects of the role of religion in their national life has been valuable. Like all perspectives, however, they have often concealed as much as they have revealed. Canadian church historians, of course, have been aware of the limitations which these perspectives have placed upon the story of the religious development of Canadian society. Their comments and criticisms, however, have never been systematically studied nor viewed in the wider context of the development of these perspectives elsewhere. This neglect needs to be remedied for such a study throws light not only on an aspect of the intellectual history of Canada but also on a number of points of emphasis in the use of these perspectives which appear to be distinctively Canadian. In what follows, therefore, an attempt has been made first of all to trace the development and continuing influence of these perspectives on the interpretation of religion in Canadian society; secondly, to assess the adequacy and limitations of these perspectives as interpretive frameworks in the Canadian context; and finally, to point out some of the factors in the present situation which need to be taken into consideration in the development of a new perspective.